City Consequences of Millennials Generation Financial Literacy: A Meta-Analytic Studies - Riani, Lilia Pasca; Sari, Novita Erliana; Prastyaningtyas, Efa Wahyu (International Business Management - Universitas Ciputra, 2024)
During the period from 2030 to 2040, Indonesia is expected to experience a demographic bonus, with 60% of its population being of productive age. This presents significant opportunities for rapid economic growth and development. However, unprepared human resources and low public financial literacy, which lead to unwise decisions in response to technological advances, remain classic issues that must be addressed. Although online transactions and financial technology provide convenience, they also have negative consequences. Consequently, this research aims to confirm the impact of financial literacy on the millennial generation through a meta-analysis study. This study employs a systematic review method, synthesizing results from 60 relevant research journals collected from January 2000 to February 2022. Data were analyzed using JASP software, following the meta-analysis procedures, which include error correction, effect size calculation, and publication bias evaluation. The results corroborate previous research, emphasizing that better financial literacy significantly influences various aspects of an individual's life, including saving behavior, consumption patterns, investment interest, risk mitigation strategies, and retirement planning. These findings underscore the critical role of financial literacy in promoting wiser financial decisions and ensuring a more stable financial future for individuals and businesses.